Investigation of the Usability of Perlite Waste for Dyestuff Removal from Aqueous Solution - Uğur Selengil; Tijen Ennil Bektaş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, unexpended perlite waste obtained from afactory producing expanded perlite was used as adsorbent. Malachite green (MY),which is a cationic dyestuff, was used as adsorbed material. The pore properties includingthe BET surface area, pore volume and average pore diameter were characterized. Thechemical composition of the perlite was analysed by XRF. The effects of initial pH,the amount of adsorbent, contact time and initial dyestuff concentration wereexamined. The adsorption kinetics of dyestuff obeys the pseudo second-order kinetic model. The experimental data indicated that theadsorption isotherms are well described by the Langmuir isotherm equation. 99% dyestuff removalwas obtained under optimum conditions. As a result, it was found thatperlite waste was a suitable adsorbent for malachite green dyestuff.